Identification of the target self-antigens in reperfusion injury - Zhang, Ming (The Rockefeller University Press, 2006)
Reperfusion injury (RI), a potential life-threatening disorder, represents an acute inflammatory response after periods of ischemia resulting from myocardial infarction, stroke, surgery, or trauma. The recent identification of a monoclonal natural IgM that initiates RI led to the identification of nonmuscle myosin heavy chain type II A and C as the self-targets in two different tissues. These results identify a novel pathway in which the innate response to a highly conserved self-antigen expressed as a result of hypoxic stress results in tissue destruction.